Refusals and power dynamics in EFL: A pragmatic study of Indonesian ELLs in Aceh - Zulfikar; Masrizal Mahmud (Universitas Syiah Kuala, 2026)
This study sought to examine the patterns of refusal strategies among Acehnese-Indonesian ELLs as well as the influence of the interlocutor’s perceived power status on their strategies. The data were collected from ten final-semester English Language Education students using Discourse Completion Tasks (DCT) and follow-up interviews. The DCT responses were analyzed based on Beebe et al.’s (1990) taxonomy of refusal strategies, while interviews provided validation and further sociopragmatic reasoning. The findings show that indirect refusals were the most commonly used strategies among the ELLs, particularly excuses, explanations, and expressions of regret. This preference reflects Indonesian collectivist values that emphasize face-saving and social harmony. Although power differences had little effect on the types of refusal strategies used, participants demonstrated awareness of power relations through varying levels of politeness. Thus, perceived power status influenced how refusals were expressed rather than the strategies themselves. These results highlight the importance of incorporating pragmatic and cross-cultural training in EFL instruction to enhance learners’ communicative competence. The study contributes to a growing body of literature on interlanguage pragmatics and provides pedagogical insights for developing context-sensitive materials in English language education. In addition, the research points out the need for classroom activities that expose learners to realistic refusal situations, enabling them to practice appropriate language choices, negotiate social distance, and respond sensitively to different levels of authority in intercultural communication contexts in academic English settings.